Ocular manifestations of Fraser syndrome in children. A clinical case - T. V. Sudovskaya; L. V. Kogoleva; T. N. Kiseleva; A. N. Bedretdinov (Российский офтальмологический журнал, 2021)
A clinical case of rare genetic disease, Fraser syndrome, in a 1.5-month-old infant is presented. Fraser syndrome is a congenital pathology characterized by diverse clinical symptoms, which involves a combination of acrofacial and urogenital abnormalities and may be accompanied by cryptophtalmos (anophthalmos or microphthalmos). A complex clinical and instrumental examination of the infant revealed the following ophthalmic manifestation of the Fraser syndrome: congenital abnormalities of eyelids, reduced palpebral fissures, significant reduction of the conjunctival sac, microcornea, vitreous fibrosis and retinal detachment. Non-surgical treatment and rehabilitation of infants with congenital microphthalmos consists in stepwise ocular prosthetics.